Effect of hydrocolloids on low-fat chocolate fillings - Dias, João (2015)
The increase of diseases arising from nutritional misbehaviors in industrialized countries has caused a larger awareness for nutritional balanced products by the consumer and, consequently, by food industry. One of the challenges of industry is the quest for achieving low caloric products and keeping the same sensory properties. The aim of this work was to study the effect of different hydrocolloids in the filling of low caloric pralines, replacing creams by skimmed milk and lowering the chocolate content. Thirty-nine batches of low caloric fillings were prepared using six different hydrocolloids (carboxymethyl cellulose, xanthan gum, high methylesterified pectin, low methyl-esterified pectin, sodium alginate and iota-carrageenan), two different concentrations (0.5 and 1.0 % w/w) and three different chocolates (white, milk and dark). The rheological characterization concluded that all the low-fat fillings presented a shear-thickening behavior and both flow behavior and consistency index were correlated with hydrocolloid concentration and with the type of chocolate. The most thickening capacity for the low-fat filling was observed using alginate and iota-carrageenan. The effect of hydrocolloid on the digital image analysis presented different results, depending on the type of chocolate used in the matrix.